Hope isn't stupid : utopian affects in contemporary American literature - Grattan, Sean Austin (University Of Iowa Press, 2017)
"Hope Isn't Stupid is the first study to interrogate the neglected connections between affect and the practice of utopia in contemporary American literature. Although these concepts are rarely theorized together, it is difficult to fully articulate utopia without understanding how affects circulate within utopian texts. Moving away from science fiction -- the genre in which utopian visions are often located -- author Sean Grattan resuscitates the importance of utopianism in recent American literary history. Doing so enables him to assert the pivotal role contemporary American literature has to play in allowing us to envision alternatives to global neoliberal capitalism. Novelists William S. Burroughs, Dennis Cooper, John Darnielle, Toni Morrison, Thomas Pynchon, and Colson Whitehead are deeply invested in the creation of utopian possibilities. A return to reading the utopian wager in literature from the postmodern to the contemporary period reinvigorates critical forms that imagine reading as an act of communication, friendship, solace, and succor. These forms also model richer modes of belonging than the diluted and impoverished ones on display in the neoliberal present. Simultaneously, by linking utopian studies and affect studies, Grattan's work resists the tendency for affect studies to codify around the negative, instead reorienting the field around the messy, rich, vibrant, and ambivalent affective possibilities of the world. Hope Isn't Stupid insists on the centrality of utopia not only in American literature, but in American life as well"-- Provided by publisher
Keywords: Utopias in literature.; American fiction -- 20th century -- History and criticism.; American fiction -- 21st century -- History and criticism.; Affect (Psychology) in literature.; Hope in literature.; Ambivalence in literature.; Utopies dans la littérature.; Roman américain -- 20e siècle -- Histoire et critique.; Roman américain -- 21e siècle -- Histoire et critique.; Espérance dans la littérature.; Ambivalence dans la littérature.; utopian literature.; LITERARY CRITICISM -- American -- General.; Affect (Psychology) in literature; Ambivalence in literature; American fiction; Hope in literature; Utopias in literature; 1900-2099; Electronic books.; Criticism, interpretation, etc.